2006
DOI: 10.1002/jclp.20239
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of change in the treatment of borderline personality disorder with transference focused psychotherapy

Abstract: We address how Transference Focused Psychotherapy (TFP) conceptualizes mechanisms in the cause and maintenance of borderline personality disorder (BPD) as well as change mechanisms both within the patient and in terms of specific therapists' interventions that engender patient change. Mechanisms of change at the level of the patient involve the integration of polarized representations of self and others; mechanisms of change at the level of the therapist's interventions include the structured treatment approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
131
1
18

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(157 citation statements)
references
References 74 publications
7
131
1
18
Order By: Relevance
“…children (Fonagy, Steele, Moran, Steele, & Higgitt, 1993;Fonagy, Steele, Steele, Moran, & Higgitt, 1991;Slade, Grienenberger, Bernbach, Levy, & Locker, 2005): ),that impairments in mentalizing represent a specific deficit in patients with BPD (Fonagy et al, 1997) that can be changed in psychotherapy (Levy et al, 2006); and that extremely low reflective functioning (RF) is linked to antisocial personality disorder and may serve as a framework to understand violent behavior (Levinson & Fonagy, 2004;Taubner, Wiswede, Nolte, & Roth, 2010). Recently, Taubner and colleagues (2013) convincingly showed that the RF scale possesses sound psychometric properties.…”
mentioning
confidence: 99%
“…children (Fonagy, Steele, Moran, Steele, & Higgitt, 1993;Fonagy, Steele, Steele, Moran, & Higgitt, 1991;Slade, Grienenberger, Bernbach, Levy, & Locker, 2005): ),that impairments in mentalizing represent a specific deficit in patients with BPD (Fonagy et al, 1997) that can be changed in psychotherapy (Levy et al, 2006); and that extremely low reflective functioning (RF) is linked to antisocial personality disorder and may serve as a framework to understand violent behavior (Levinson & Fonagy, 2004;Taubner, Wiswede, Nolte, & Roth, 2010). Recently, Taubner and colleagues (2013) convincingly showed that the RF scale possesses sound psychometric properties.…”
mentioning
confidence: 99%
“…On examine aussi les changements dans les capacités de mentalisation (fonction réflexive). Ces changements sont mesurés au moyen de l'échelle de la fonction réflexive ‹ FR › développée par Fonagy (Fonagy et al, 1997 ;Levy et al, 2006). On considère enfin les changements dans la symptomatologie des patients limites au cours d'une année de PFT (Clarkin et al, 2007).…”
Section: Devis De L'étudeunclassified
“…La plupart des patients affichaient un changement dans leurs modèles opérationnels intériorisés d'attachement de non-résolu/désorganisé à organisé (insécurisant ou sécurisant) après un an en PFT (Diamond et al, 2003). Tous les patients, sauf un, affichaient des améliorations de la FR après un an en PFT (Diamond et al, 2003), un résultat qui a été reproduit dans l'étude plus globale de Levy et al (2006), dont environ la moitié des patientes ont accru leur résultat d'au moins une catégorie plus élevée de la FR, passant, par exemple d'une FR de bas niveau ou discutable à une FR ordinaire. De plus, nos analyses des données de la PT-AAI ont révélé que la plupart des patients avaient des états mentaux peu sécurisés (évitant, préoccupé ou impossible à classer) par rapport à leur théra-peute, bien que deux d'entre eux se soient aussi classés avec des états mentaux sécurisants après un an en PFT.…”
Section: Résumé Des Résultats De Rechercheunclassified
“…Así, por ejemplo, en una investigación que se mantiene actualmente en curso (Martínez, Krause, Tomicic, Altimir y Pérez, 2014), se han encontrado indicadores de la expresión de la subjetividad de paciente y terapeuta a través del discurso verbal que muestra la presencia de aspectos -denominados posiciones subjetivas-más reflexivos y mentalizadores que tendrían la función de regular el diálogo interno y externo de otros aspectos menos reflexivos y automáticos. Como sea, los buenos resultados terapéuticos están relacionados con el crecimiento de habilidades mentales que se asemejan a la mentalización, entonces la evaluación de la misma durante la psicoterapia puede constituirse en una dimensión adicional que permita comprender cómo se produce la mejoría a lo largo del tratamiento (Fonagy y Bateman, 2006;Levy et al, 2006a;2006b;Bateman y Fonagy, 2012).…”
unclassified